Diagnostic evaluation of initial enamel lesions using DIAGNOdent, color difference, and micro-CT - Chaiklahan, Pasika; Senawongse, Pisol; Pudla, Matsayapan; Klaophimai, Arthit; Thongbai-on, Nathamon (Mahidol Dental Journal, 2025)
Objectives: This study aimed to evaluate the relationship between lesion depth of the initial stages of enamel demineralization measured by a laser fluorescence device (DIAGNOdent), and high-resolution Micro- CT imaging, and to assess color differences (ΔE) as potential indicators of demineralization depth. Materials and Methods: Thirteen human premolars were prepared and subjected to a controlled remineralization and demineralization regimen to simulate initial enamel lesions. Following a series of immersion cycles, specimens were analyzed for DIAGNOdent values, ΔE, and lesion depth through Micro-CT imaging. Results: The results demonstrated a significant positive correlation between DIAGNOdent readings and lesion depth from micro-CT scan (p<0.01, r = 0.79), as well as between ΔE values and lesion depth (p<0.01, r = 0.79). Thus, both DIAGNOdent and ΔE analysis proved effective in assessing enamel demineralization. Conclusions: This approach reveals the utility of combining advanced diagnostic tools to improve the understanding of early enamel demineralization and underscores the necessity for early detection and intervention in clinical practice to mitigate the progression of dental caries.